1994
DOI: 10.3146/i0095-3679-21-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Weather-Based Spray Advisory for Management of Early Leaf Spot of Peanut in Oklahoma1

Abstract: A simplified version of the weather-based advisory program developed by Pawin, Smith, and Crosby (PSC) for scheduling fungicide sprays for management of early l e d spot (Cercospora arachidicoh Hori) of peanut (Arachis hypogea L.) was evaluated under various productions systems in Oklahoma from 1990-1992. Over eight trials with spanish cultivars, the number of sprays per season averaged 5.7 for the 14-d schedule and 4.0 for the advisory program. Final disease incidence (symptomatic and defoliated leaflets) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
8
1
Order By: Relevance
“…In addition to temperature and precipitation, relative humidity is another weather variable that has been shown in many studies to be related to the development of fungal pathogens (Damicone et al, 1994;Boyle, 1965, 1966;Jewell, 1987;Olatinwo et al, 2008Olatinwo et al, , 2009Olatinwo et al, , 2011Shew et al, 1988;Wu et al, 1999). In monitoring the likelihood of infection initiation through sporulation of fungal spores, the available moisture on a leaf surface can be estimated using relative humidity, since it correlates with wetness of a leaf surface within a canopy.…”
Section: Weather Factors and Derived Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to temperature and precipitation, relative humidity is another weather variable that has been shown in many studies to be related to the development of fungal pathogens (Damicone et al, 1994;Boyle, 1965, 1966;Jewell, 1987;Olatinwo et al, 2008Olatinwo et al, , 2009Olatinwo et al, , 2011Shew et al, 1988;Wu et al, 1999). In monitoring the likelihood of infection initiation through sporulation of fungal spores, the available moisture on a leaf surface can be estimated using relative humidity, since it correlates with wetness of a leaf surface within a canopy.…”
Section: Weather Factors and Derived Variablesmentioning
confidence: 99%
“…Examples of internetbased interactive systems include the potato late blight in Michigan (http://www.lateblight. org/forecasting.php) described by Wharton et al (2008); the AWIS Weather Services, Inc (http://awis.com); the Oklahoma mesonet peanut leaf spot advisor (http://www.mesonet.org/index.php/agriculture/category/ crop/peanut/leaf_spot_advisor) based on a model described by Damicone et al (1994); North American Plant Disease Forecast Center, North Carolina State University (http://cdm. ipmpipe.org/); HortPlus (http://www.hortplus.com/Brochure/MetWatch/MWSoftware.…”
Section: Existing Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of weather information in most models is typically obtained from several sources, including the National Weather Service or observational weather networks such as the Automated Environmental Monitoring Network (AEMN; www.georgiaweather.net), which is the largest automated weather station network in the southeastern USA (Hoogenboom 2000(Hoogenboom , 2001Hoogenboom et al 2003). Weather observations from similar regional networks have been used in disease prediction models, as documented in many studies including for potato light blight in Michigan (Wharton et al 2008), peanut leaf spot in Oklahoma (Damicone et al 1994), and as a web-based tool for risk assessment of Fusarium head blight (http:// www.wheatscab.psu.edu).…”
Section: Introductionmentioning
confidence: 99%
“…The study also confirmed a correlation between leaf spot and a weatherdependent infection index previously described by Jensen and Boyle (1966). Some disease models including the Oklahoma peanut leaf spot model developed by Damicone et al (1994) were based in part on the earlier work of Jensen and Boyle (1966). The Oklahoma peanut leaf spot model calculates the daily "infection hours" based on 24 h of temperature, and leaf wetness or relative humidity.…”
Section: Introductionmentioning
confidence: 99%